Etiology Of Breast Cancer (Journal of Pharmaceutical Negative Results, 2023)
Breast cancer is a fusion, diverse, and composite disease of women. There is no sole cause of breast cancer. The Origin of breast cancer are not perfectly known. However, there are many predisposing factors known to affect possibility of developing breast cancer. The risk of breast cancer has been compatible associated with age, a family or genetically history of breast cancer, History of early menarche, Delayed age first pregnancy, short  period or no breastfeeding, and  late menopause, Prolonged period of hormonal  therapy (HT), alcohol consumption, sedentary lifestyle, exposure to ionizing radiation like X-rays, and genetic predisposition. Mutations in inherited high penetrance genes can cause only 5–10% of all types of breast cancers.